Exploring city spaces : an exploration into mapping practices and rule based design - Tayob, Huda (School of Architecture, Planning and Geomatics, 2016)
This paper has been written in 3 sections. With some adjustments, the first section is largely the theory paper, the second my technology paper, and the third an exploration of my design. These three sections have been written as disparate parts. Ideas and themes are carried through the three papers, but they do not read as a coherent whole. This year has been a journey into the city of Cape Town; an exploration of its complexity, vibrant city spaces and everyday life. This is essentially what this paper is about, and is a theme that is explored in all three sections in different ways- with the third drawing and building on the first two. I started with ideas of Lefebvre and the work of CHORA as a methodology for exploring the 'everyday practices' in the city- and moved through this to an engagement with rule based design and algorithmic architecture. The design chapter loops back to the beginning of the paper, and draws from and is informed by both the initial research, a'1d rule- based methodology. All three of these sections have been exploratory processes engaging with this set of ideas around complexity within the city. I do not see them as providing an answer as to how to design or explore cities, but rather as an attempt to engage with these very real questions. They are a series of ideas that have enabled me to see parts of the 'hidden world' within Cape Town, and explore this through ideas of the unknown and unimaginable in architecture.